Hacker and Moore's essentials of obstetrics and gynecology - Gambone, Joseph C; Hacker, Neville F; Hobel, Calvin J (Saunders/Elsevier, 2016)
Get guidance on evaluation, diagnosis, and management of a wide range of obstetric and gynecologic disorders from the most comprehensive and concise reference on the subject. The 5th Edition of this popular and practical resource features additional clinical photos and material on vaccination and disease prevention. The full-color design with illustrations and photographs complement the text. . Features a full-color design and images for a visually accessible guide that easily correlates to actual clinical experience. Delivers must-know information efficiently and effectively through a concise, clear writing style. Features a chapter on vaccination and disease prevention and origin for increased clinical focus and utility. Incorporates more clinical photographs for a clearer visual presentation of clinical applications. Reflects changes in the APGO/CREOG objectives through updated content
"A student Consult title"--Cover
Keywords: Gynecologie; Obstetrics; Genital Neoplasms; Gynecology; Obstetrique; Pregnancy complications